Burden and quality of life in caregivers of obsessive-compulsive disorder and schizophrenia: a cross-sectional study - Afzal, M.; Mohanty, Sandhyarani; Sisodia, Anil Kumar (International Journal of Research in Medical Sciences, 2021)
Background: Obsessive–compulsive disorder (OCD) and schizophrenia both are chronic and disabling mental illness which imposes considerable burden on caregivers. Many studies have also reported that both of them have a negative impact on the quality of life (QOL) of both the patients and the caregivers living with the patients. The aim of the study was to assess and compare the burden of care and quality of life (QoL) in the care givers of patients with Obsessive–Compulsive Disorder (OCD) and Schizophrenia. Methods: The present study is a hospital based, cross-sectional and comparative study. 30 patients with schizophrenia and 30 Obsessive-Compulsive Disorder patients and their caregivers attending the OPD and family ward of Institute of Mental Health and Hospital, Agra were selected through purposive sampling with specific inclusion and exclusion criteria. World Health Organization Quality of Life Scale (BREF version), Burden Assessment Schedule, Positive and Negative Syndrome Scale (PANSS), Yale–Brown Obsessive Compulsive Scale (Y-BOCS) were used for assessment. Results: The findings of this study revealed remarkable burden in the caregivers of OCD and Schizophrenia patients along with considerable and comparable impairment of their quality of life. Caregivers of Schizophrenia patients experienced more burden and have poor quality of life than the caregivers of OCD patients. Conclusions: It is suggested to develop effective strategies for family intervention with the purpose of supporting the caregivers and improving their quality of life.